Implementasi Augmented Reality Pembelajaran Bahasa Batak pada Pengenalan Perabotan Dapur Menggunakan Aksara Batak bagi Anak-Anak dengan Algoritma Fast Corner Detection - Roni Pardede; Ari Usman; Nur Wulan (Journal on Education, 2025)
This research aims to develop an augmented reality (AR) learning system which aims to introduce the Toba Batak language to children while understanding the use of Batak script in the context of kitchen furniture. The application of the Fast Corner Detection algorithm is used to improve corner detection capabilities in the resulting AR images. This research consists of several stages, including collecting Toba Batak script data, developing 3D models of kitchen furniture, and implementing the Fast Corner Detection algorithm in an AR environment. The research results show that the application of AR in learning the Toba Batak language can increase children’s interest and understanding of Batak language and culture. In addition, the use of the Fast Corner Detection algorithm provides sufficient corner detection results to ensure good visual quality in AR experiences. It is hoped that this research can contribute to the development of innovative educational technology to preserve regional language and culture, especially the Toba Batak language, while providing an interesting learning experience for children.